(untitled) (Experimental biology, 2023)
Parasitic organisms, being an integral part of natural and technogenically transformed ecosystems, can serve as indicator species that reflect the impact on the environment, reacting to changes in the habitat with changes in physiology or chemical composition. Ectoparasites, due to the fact that they can interact with the environment in various ways, they are able to provide information about the hydro- and geochemical background of the environment due to their presence or absence. Endoparasites, in turn, are less susceptible to toxic substances, demonstrating the ability to accumulate environmental toxicants inside their tissues. The state of the environment has a significant impact on parasites, determining their quantitative and qualitative indicators of the population structure. In this regard, there is a need for systematic monitoring of ichthyoparasitological studies in the reservoirs of Northern Kazakhstan, using fish parasites as indicator species. The article presents the data of ichthyoparasitological studies conducted in the reservoirs of Northern Kazakhstan (Akmola, Pavlodar and North Kazakhstan regions), as a result of which 23 species of parasitic organisms were identified, including 1 species of zoonotic (Raphidascaris acus) and 2 species of highly virulent (Gyrodactylus cyprini, Schyzocotyle acheilognathi) helminths. Gyrodactylus cyprini, Gyrodactylus cernuae, Eudiplozoon sp., Diplostomum paraspathaceum, Diplostomum chomatophorum were first established for reservoirs of northern Kazakhstan. In the backwater of the Chernoyarsk basin, the Irtysh can be considered unfavorable for ergasileous parasitosis.